Inhibition of MMP-9-dependent Degradation of Gelatin, but Not Other MMP-9 Substrates, by the MMP-9 Hemopexin Domain Blades 1 and 4 - Ugarte-Berzal, Estefanía (J Biol Chem, 2016)
Degradation and remodeling of the extracellular matrix by matrix metalloproteinases (MMPs) plays important roles in normal development, inflammation, and cancer. MMP-9 efficiently degrades the extracellular matrix component gelatin, and the hemopexin domain of MMP-9 (PEX9) inhibits this degradation. To study the molecular basis of this inhibition, we generated GST fusion proteins containing PEX9 or truncated forms corresponding to specific structural blades (B1–B4) of PEX9. GST-PEX9 inhibited MMP-9-driven gelatin proteolysis, measured by gelatin zymography, FITC-gelatin conversion, and DQ-gelatin degradation assays. However, GST-PEX9 did not prevent the degradation of other MMP-9 substrates, such as a fluorogenic peptide, αB crystalline, or nonmuscular actin. Therefore, PEX9 may inhibit gelatin degradation by shielding gelatin and specifically preventing its binding to MMP-9. Accordingly, GST-PEX9 also abolished the degradation of gelatin by MMP-2, confirming that PEX9 is not an MMP-9 antagonist. Moreover, GST-B4 and, to a lesser extent, GST-B1 also inhibited gelatin degradation by MMP-9, indicating that these regions are responsible for the inhibitory activity of PEX9. Accordingly, ELISAs demonstrated that GST-B4 and GST-B1 specifically bound to gelatin. Our results establish new functions of PEX9 attributed to blades B4 and B1 and should help in designing specific inhibitors of gelatin degradation.